1994
DOI: 10.1148/radiology.190.2.8284409
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic CT images: effect of lossy image compression on diagnostic accuracy.

Abstract: The techniques presented for evaluation of image quality do not depend on the specific compression algorithm and provide a useful approach to evaluation of the benefits of any lossy image processing technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 39 publications
1
36
0
Order By: Relevance
“…CT images generally exhibit lower tolerance to compression than plain radiographs [5,7,14,15]. The acceptable compression level was reported to be as high as 8:1 to 20:1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CT images generally exhibit lower tolerance to compression than plain radiographs [5,7,14,15]. The acceptable compression level was reported to be as high as 8:1 to 20:1.…”
Section: Discussionmentioning
confidence: 99%
“…The acceptable compression level was reported to be as high as 8:1 to 20:1. These reported thresholds include 8:1 for the diagnosis of acute appendicitis (using a wavelet compression algorithm) [16], 9:1 for the detection of mediastinal adenopathy and pulmonary nodules (tree-structured vector quantization) [14], 10:1 for the detection of focal hepatic lesions (a threedimensional wavelet) [7], 10:1 for nodule detection at lowdose chest CT (JPEG 2000) [17], 10:1 for the detection rate of small lung cancers at low-dose CT (JPEG and a wavelet) [18], 10:1 for the measurement of pulmonary nodule volume at low-dose CT (JPEG 2000) [19], 20:1 for the diagnosis of coronary artery calcification (JPEG and a wavelet) [15], 20:1 for the detection of acute cerebral infarction (JPEG) [20], and 20:1 for the detection of polyps at CT colonography (a wavelet) [21].…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies that evaluate the eect of image compression on diagnostic ability in body CT. Cosman et al 9 found that compression levels of 9:1 did not impair diagnosis of mediastinal adenopathy or pulmonary nodules on CT images. Goldberg et al 11 looked at the eect of varying compression levels on the ability to detect hepatic space occupying lesions.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,22 This study was undertaken to evaluate the eect of varying compression levels on the ability of radiologists to make a CT diagnosis of acute appendicitis, the presence of which is detected by the perception of subtle dierences in contrast. Appendicitis is common, the CT accuracy is well known from multiple published studies, 6,14 and rapid surgical veri®cation is possible.…”
mentioning
confidence: 99%
“…Previous studies of the effects of lossy compression on diagnostic accuracy have focused on the detection of structures [5,7,8,15,19,26]. However, measurement tasks also play a crucial role in diagnostic radiology.…”
Section: Mr Study: Example Of Measurement Accuracymentioning
confidence: 99%